Challenges of radical chemoradiation planning in Stage III non-small-cell lung cancer: Can volumetric modulated arc radiotherapy overcome an unfavourable location?. (January 2020) - Kapoor, Rakesh; Das, Namrata; Miriyala, Raviteja; Sood, Ashwani; Oinam, Arun; Singh, Navneet
Highlights: Subset of Stage III Non-Small Cell Lung Cancer patients are not fit for upfront chemoradiotherapy. Spatial location of disease burden hinders radiotherapy treatment planning due to organs at risk. Prediction based on disease location requiring VMAT to circumvent this problem necessary. Abstract: Background and purpose: Radiotherapy treatment planning of radical doses for concurrent chemoradiation in Stage III non-small-cell lung cancer (NSCLC) presents many challenges. This dosimetric study aimed to analyse the impact of spatial location of tumour and nodal burden in limiting the achievement of normal organ constraints and the use of appropriate radiotherapy technique to address it. Materials and methods: Fifteen Stage III NSCLC patients underwent 18 F-fluorodeoxyglucose-positron emission tomography (FDG-PET)/computed tomography (CT) based treatment planning. VMAT (Volumetric Modulated Arc Radiotherapy) plans were made for all patients treated by 3D-CRT (3-Dimensional Conformal Radiotherapy). A binomial logistic regression was performed to ascertain the tumour and nodal characteristics that decreased the likelihood of being planned to 60 Gy. Results: Inability to achieve normal tissue constraints, particularly spinal cord dose to less than 50 Gy, during initial planning by the assigned treatment technique was the primary dose limiting factor in four patients (p = 0.02). Alternate VMAT plans could achieve the dose constraints where 3D-CRT was unsuccessful in patients with bulky central disease in two patients. This technique fell short when there was gross vertebral body erosion. Conclusions: For tumours with bulky central disease, VMAT should be preferred. With gross vertebral body erosion, even VMAT falls short if the planning target volume includes the spinal cord. In a subset of Stage III NSCLC upfront chemoradiation to radical doses may not be feasible.